Model Kepemimpinan Spiritual dalam Manajemen Pendidikan di Era Artificial Intelligence: Studi di Pondok Pesantren Gedangan - Muqoffi; Wafa, Ali; Shofi (re-JIEM (Research Journal of Islamic Education Management), 2026)
The development of Artificial Intelligence has brought significant changes to the education system, including in Islamic boarding schools. This study aims to analyze the integration of spiritual leadership values ​​with the use of Artificial Intelligence in educational management and to formulate an effective spiritual leadership model to improve the quality of educational management at Gedangan Islamic Boarding School. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation studies. Data analysis was conducted thematically through the stages of data reduction, data presentation, and conclusion drawing. The results show that the integration of spiritual leadership values ​​with the use of Artificial Intelligence is carried out by positioning technology as a learning support tool that remains based on the spiritual values ​​of Islamic boarding schools. The spiritual leadership model is realized through four main principles: academic integrity in the use of artificial intelligence, selectivity in filtering digital information, exemplary behavior in the ethical and proportional use of technology, and scientific deepening by making artificial intelligence a learning aid, not a substitute for scientific authority. These findings indicate that spiritual leadership is capable of shaping ethical, selective, and constructive technology utilization governance in Islamic boarding school education management in the era of Artificial Intelligence.